2008
DOI: 10.1159/000184705
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation in metabolic phenotypes

Abstract: Despite successes in identifying genetic contributors to common metabolic phenotypes, only part of the heritable component of these traits has thus far been explained. Copy number variation (CNV) is likely to be responsible for some of the unexplained variation. As observed with single nucleotide changes, it is probable that both rare and common CNVs will contribute to susceptibility to metabolic disease. For instance, CNVs in the LDLR gene underlie a substantial portion of disease in patients with heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…It was found that the low-density lipoprotein receptor gene (LDLR) is found to be affected in the patients with familial hypercholesterolemia. 53,54 CNV AND METABOLIC DISEASES Type 2 diabetes Type 2 diabetes is a chronic metabolic disorder characterized by high glucose level or insulin resistance. Various SNPs have been linked to the high risk for diabetes but other genetic variations such as CNV were not explored.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…It was found that the low-density lipoprotein receptor gene (LDLR) is found to be affected in the patients with familial hypercholesterolemia. 53,54 CNV AND METABOLIC DISEASES Type 2 diabetes Type 2 diabetes is a chronic metabolic disorder characterized by high glucose level or insulin resistance. Various SNPs have been linked to the high risk for diabetes but other genetic variations such as CNV were not explored.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…In addition, CNV analysis has revealed a number of additional causative mutations in the LDLR gene in patients with familial hypercholesterolemia (Reviewed by [82]). Relatively rare CNVs identified in the LPL, LIPC and LIPG genes were found to be associated with loss of enzymatic activity [83]. No association between HL and CAD has been found by GWAS.…”
Section: Genome Wide Association Studiesmentioning
confidence: 99%
“…Copy number variations (CNV), deletions and duplications, have gained most attention due to their generality and potential dosage effect and because they are easier to assay. Recent estimates report that about 40% of the known genes are overlapped by CNVs ( 197 ).…”
Section: Structural Variation and Its Potential Role In Hdl-c Geneticsmentioning
confidence: 99%
“…These fi ndings suggest that rare CNVs could also underline the HDL defi ciency cases with no known causative mutations. Likewise, a common CNV in the lipoprotein(a), kringle IV, has been shown to account for ‫ف‬ 50% of the variation in plasma lipoprotein(a) levels ( 197 ). However, as of yet, CNVs (rare and common) have not been comprehensively explored in genetic studies for lipids, mainly because of the challenges in yielding accurate genotypes ('CNV calling') required for association analysis (as opposed to the lower accuracy needed for CNV discovery) ( 201 ).…”
Section: Structural Variation and Its Potential Role In Hdl-c Geneticsmentioning
confidence: 99%